Cephalopod limestone biofacies on the northern slopes of the Silurian volcanic archipelago in the Prague Basin containing re-described benthic Cardiola donigala-Slava cubicula Community (Bivalvia, Barrandian, Bohemia) - Kriz,J. (Journal of the Czech Geological Society, 1999)
Origin and palaeoecology of the upper Gorstian (Silurian) cephalopod limestone biofacies on the northern slopes of the Silurian volcanic archipelago in the Prague Basin (Barrandian, Bohemia) and the benthic Cardiola donigala-Slava cubicula Community is described. The history of the old collector's pits at the locality of the cephalopod limestone Lodenice-Sedlec is discussed.
Keywords: Bohemia; Silurian; Gorstian; Barrandian; Prague Basin; Cephalopod Limestones; Palaeoecology; History